Genetics of dominant gibberellin-insensitive dwarfism in maize. - Harberd, N; Freeling, M (1989)
D8 and Mpl1 are two dominant dwarfing mutations of maize. Although they differ in severity of dwarfism, both D8 and Mpl1 mutants are unresponsive to gibberellin (GA). Because of their close phenotypic resemblance to the recessive GA-sensitive dwarf mutants these dominant mutations may identify a gene whose product is involved in the reception of GA. With this possibility in mind we have studied the genetic properties of D8 and Mpl1. Both mutations map close to Adh1 on chromosome 1L. By marking normal and translocated 1L arms with different Adh1 electrophoretic mobility alleles, we investigated the effect of gene dosage on dominant dwarf phenotype. The results suggest that D8 and Mpl1 encode novel product functions and that these functions are relatively insensitive to the presence of the (presumed) wild-type product. Using X-ray induced chromosome breakage we created sectors of wild-type cells within D8 or Mpl1 tissue; these sectors were marked by the linked recessive lw mutation. The phenotypes of these sectors demonstrated that, at least in certain plant organs and tissues, dominant dwarfism can be an autonomous phenotype. These results are consistent with the hypothesis that the wild-type gene product acts as a GA receptor. The potential utility of dominant dwarf phenotype in plant developmental analysis is discussed, and possible mechanisms for the action of the D8 and Mpl1 mutations are considered.